2010
DOI: 10.1097/eja.0b013e3283340a81
|View full text |Cite
|
Sign up to set email alerts
|

The supraglottic airway I-gel in comparison with ProSeal laryngeal mask airway and classic laryngeal mask airway in anaesthetized patients

Abstract: I-gel may have a similar airway sealing to that of pLMA, higher than that of cLMA, and is not associated with adverse events. The I-gel might be an effective alternative as a supraglottic airway device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 20 publications
13
70
0
3
Order By: Relevance
“…In this study, the first-attempt insertion success rate was significantly higher in the rotation group than in the standard group. This success rate is consistent with previous reports, in which the primary success rate for i-gel insertion with the standard technique was 78-93% [8,10,17]. Our previous reports comparing two insertion techniques for the ProSeal LMA showed that the success rate at the first attempt was significantly higher in the rotation group than in the standard technique group [13][14][15], similar to the present study using the i-gel.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, the first-attempt insertion success rate was significantly higher in the rotation group than in the standard group. This success rate is consistent with previous reports, in which the primary success rate for i-gel insertion with the standard technique was 78-93% [8,10,17]. Our previous reports comparing two insertion techniques for the ProSeal LMA showed that the success rate at the first attempt was significantly higher in the rotation group than in the standard technique group [13][14][15], similar to the present study using the i-gel.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence of i-gel insertion failure was 4.4% in this study. Similar incidence rates were reported in previous studies, in which the overall failure rate for i-gel insertion was 0-4% [8,10]. The main reason for fail- ure to insert the ProSeal LMA or i-gel is impaction at the back of the mouth by tongue folding [11,12,18].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations